2014
DOI: 10.1111/pcn.12226
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating subjective domains of antipsychotic‐induced adverse effects using heart rate variability

Abstract: Aims Antipsychotic‐induced autonomic dysregulation may lead to a wide range of subjective side‐effects in schizophrenia patients. Using heart rate variability (HRV) measures, we prospectively examined the relationship between subjective side‐effects and cardiac autonomic regulation in unmedicated schizophrenia patients. Methods Forty‐five unmedicated schizophrenia patients were assessed for antipsychotic‐associated side‐effects and HRV parameters at baseline and after 6 weeks of treatment. Psychiatric symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…However, this relationship has not been fully studied and some studies has conflicting results [1,2]. Several studies found more excess cardiovascular dysfunction in Schizophrenia patients than in control [3,4], and cardiac failure including suicidal action [5]. Recent attention has focused on the ISSN: 2332-3469 length is varied using frequency generator and the light indicator automatically divides the cycle length into 40% inhalation and 60% exhalation [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, this relationship has not been fully studied and some studies has conflicting results [1,2]. Several studies found more excess cardiovascular dysfunction in Schizophrenia patients than in control [3,4], and cardiac failure including suicidal action [5]. Recent attention has focused on the ISSN: 2332-3469 length is varied using frequency generator and the light indicator automatically divides the cycle length into 40% inhalation and 60% exhalation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Others have shown that people with schizophrenia have decreased HRV compared to the general population (J. S. Chang et al, 2009;Clamor et al, 2016;Liu et al, 2021;Montaquila et al, 2015;Quintana et al, 2016). Moreover, decreased HRV has been associated with greater likelihood of negative symptoms (J. S. Kim et al, 2004), and general psychopathology symptoms (Benjamin et al, 2020;J. S. Chang et al, 2015) as rated on the PANSS.…”
Section: Bridging Cardiac Dysfunction With the Brain And Outcomementioning
confidence: 99%